Evaluating the Quality of Religious Moderation: A Case Study of Students in Public High Schools - Muhammad Ihsan Nashihin; Faisal Sundani Kamaludin; Syariful Syariful; Ahmad Faizudin (Institut Agama Islam An-Nawawi Purworejo, 2024)
The aim of this study is to assess the degree of religious moderation among high school students. There are many cases of intolerance and violence between students in South Jakarta, that require a solution in the form of an attitude of religious moderation. Religious moderation, within the Indonesian context, represents a balanced approach to religious practices and beliefs, promoting harmony within the pluralistic Indonesian society. It encompasses an individual's commitment to religious principles, interactions within a diverse community, and civic responsibilities. Religious moderation teaches to have attitudes and actions in middle proportion. This research employs a quantitative approach with a descriptive methodology. Data is primarily collected through a structured questionnaire. The study's population consists of high school seniors in South Jakarta, with a representative sample drawn from five schools in the region. The findings reveal an overall mean score of 81.38 on a 0-100 scale, indicating a